The Influence of Online Learning Using Smansa Ende Online On Motivation and Results of Physics Learning of Class XI - Alung, Helena V; Kaleka, Melkyanus Bili Umbu; Rahmawati, Ana Silfiani (Journal of Science Education Research, 2022)
This study aims to determine the effect of online learning using Smansa Ende online on motivation to learn physics, knowing the effect of online learning using SMANSA ENDEonline on physics learning outcomes, in class XI students of SMA Negeri 1 Ende in the 2020/2021 academic year. The type of research used is quantitative research by examining causal relationships that are not given treatment by researchers and carried out on activities that have occurred. This study obtained data through questionnaires and documentation. The population in this study were students of class XI MIPA 4 and XI MIPA 5 at SMAN 1 Ende, totaling 71 students with a sample of 36 students in class XI MIPA 5 . The results of hypothesis testing using linear regression t test show that H1 and H2 are accepted, with a significance value of H1 less than 0.05 (0.026 less than 0.050) then there is an effect of online learning using Smansa Ende Online on learning motivation. While the significant value of H2 is less than 0.05 (0.007 less than 0.050) then there is an effect of online learning using Smansa Ende Online on learning motivation. Keywords: Online Learning, Learning motivation, learning outcomes.